2003
DOI: 10.1108/01443570310496661
|View full text |Cite
|
Sign up to set email alerts
|

Jump‐starting continuous improvement through self‐assessment

Abstract: The innumerable accounts of successful implementation of kaizen in Japan during more than 40 years has led to the expectation that continuous improvement (CI) might offer companies a means to gain and maintain a competitive advantage in the turbulent 1980s and 1990s. However, the majority of CI initiatives within the US and Europe died within a few years. While explanations as to why these efforts have not been successful can be found in the literature, methods for rejuvenating stagnant CI programs are still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
30

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 17 publications
3
84
0
30
Order By: Relevance
“…This supported individuals in 'unlearning' out-dated practices, changing their perceptions and accepting new modes of practice. This is consistent with the findings from the PI (Bateman and Rich 2003), CI (Jørgensen et al 2003, Lam et al 2015 and OL (Fiol and Lyles 1985) literatures that identified such factors as important barriers to learning and sustained improvement.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This supported individuals in 'unlearning' out-dated practices, changing their perceptions and accepting new modes of practice. This is consistent with the findings from the PI (Bateman and Rich 2003), CI (Jørgensen et al 2003, Lam et al 2015 and OL (Fiol and Lyles 1985) literatures that identified such factors as important barriers to learning and sustained improvement.…”
Section: Discussionsupporting
confidence: 90%
“…Notwithstanding the need to embed improvement practices in order to achieve CI, Zangwill and Kantor (1998) noted how benefits from improvement activities could reduce over time as inefficiencies were removed from processes. Lee et al (2000), Jørgensen et al (2003) and Bateman (2005) identified the support and involvement of management, improvement goals, measures, and being provided with sufficient resources, as key enablers to sustain PI and achieve CI. Bessant and colleagues (Bessant et al 1994, Bessant and Francis 1999, Bessant et al 2001) identified similar topics of strategic leadership, tools and techniques, in addition to rewards and recognition.…”
Section: Pi and CI In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Working as groups, while utilizing appropriate problem solving techniques, it will increase efficiency and pride in work improvement outputs [13] . Jorgensen et al [14] , examine the role of the team leader in continuous improvement. In their longitudinal case study based in Denmark, it is identified that there was a gap in perception between the senior management and team leaders in terms of enablers that were in place.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Imai (1986: xxix) defines it as ‗ongoing improvement involving everyone -top management, managers, and workers'. Other authors share this view of equating kaizen with continuous improvement explicitly (Aoki, 2008;Malloch, 1997;Styhre, 2001) or implicitly (Bessant et al, 2001;Dobosz-Bourne & Jankowicz, 2006;Jørgensen et al, 2003). Brunet and New (2003) discuss the ambiguity and inconsistency of the way kaizen is described in the literature.…”
Section: Proxy Of Kaizen: Personal-initiativementioning
confidence: 99%